2019
DOI: 10.1101/602730
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oregano essential oil vapour preventsPlasmopora viticolainfection in grapevine (Vitis Vinifera) by triggering autoimmune metabolic pathways

Abstract: The reduction of synthetic fungicides in agriculture a major challenge in maintaining sustainable production, protecting the environment and consumers’ health. Downy mildew caused by the oomycete Plasmopora viticola is the major pathogen in viticulture worldwide and responsible for up to 60% of pesticide treatments. Alternatives to reduce fungicides are thus utterly needed to ensure sustainable vineyard-ecosystems, consumer health and public acceptance. Essential oils (EOs) are amongst the most promising natur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 99 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…Moreover, much evidence revealed that NAC genes play important roles in plant resistance including abiotic and biotic stress responses [128]. VvNAC36 (VIT_03s0038g03410), which was identified as a powdery mildew dependent gene and may be part of defense system [129], was found to be upregulated within T2 infected berries at both stages.…”
Section: Gld Modulation Of Transcription Factors (Tfs)mentioning
confidence: 99%
“…Moreover, much evidence revealed that NAC genes play important roles in plant resistance including abiotic and biotic stress responses [128]. VvNAC36 (VIT_03s0038g03410), which was identified as a powdery mildew dependent gene and may be part of defense system [129], was found to be upregulated within T2 infected berries at both stages.…”
Section: Gld Modulation Of Transcription Factors (Tfs)mentioning
confidence: 99%